International migration and its contribution in the transmission of malaria in the Zimbabwean border districts. - Chiruvu, Roy; Matare, Takura; Nmehielle, Nkechi-Obisie-; Gombe, Notion T; Mhlanga, Maxwell; Ndaimani, Augustine (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Objective: This study aimed to provide evidence for policy and programming on malaria in Zimbabwe and other sub-Saharan countries. It also aimed to provide insight on how best to improve cross border collaborations in the prevention and control of malaria. Design and setting: A cross sectional mixed methods study design using both quantitative and qualitative approaches was conducted from February to April 2016 in the selected health facilities in Mutare and Mutasa districts of Zimbabwe. Quantitative methods included record review of administrative registers from 2012 to 2015 in the participating health facilities in the border districts of Mutasa and Mutare. Data on malaria test, the result of the malaria tests and sociodemographic data were abstracted from the register. Qualitative methods comprised of focus group discussions (FGDs) with the health centre committee members, patients (both sexes in one FGD) in the health facilities. A sample of 318 patient records was selected through purposive sampling.Univariate and bivariate analysis were done using Epi Info 7. Thematic analysis was employed in the analysis of qualitative data. Main outcome: The main outcome measure was the level of malaria attributable to international migration. Results: The proportion of malaria cases from Mozambique treated in Zimbabwe rose from 2.7% in 2013 to 5.1% in 2015. Males constituted 60% of patients from Mozambique and 75.5% of the patients aged from 5-34 years. Older children (12-59 months) were more susceptible to infections compared to younger ones. Being male (OR 1.29, 95% C.I 1.12-1.42) and being less than 5 years (OR 1.23 95%C.I 1.10-1.38) were significant risk factors for malaria transmission in Mutasa and Mutare. Participants in FGDs cited climate change as the main cause of an increase in malaria transmission. Other factors cited include resistance to indoor residual spraying; ineffective chemicals; poor diagnosis and insufficient drugs. Conclusions: The study revealed that international migration is a significant contributor to malaria transmission across bordering districts in Zimbabwe. It is imperative that the sub-Saharan governments intensify collaborative malaria prevention and control action and strategies. There is great need for continuous entomological surveillance to ensure that the different interventions across the countries are effectively managed through an evidence based approach.